A Dynamic Rupture Source Model for Very Low‐Frequency Earthquake Signal Without Detectable Nonvolcanic Tremors. Issue 21 (13th November 2019) - Wu, Baoning; Oglesby, David D.; Ghosh, Abhijit; Li, Bo
Abstract: A very low‐frequency earthquake is a type of seismic event that is rich in low frequencies and depleted in higher frequencies compared to regular fast local earthquakes of similar magnitude. The source process behind very low‐frequency earthquakes is still poorly understood. Here we present a dynamic rupture source model for very low‐frequency earthquake signal without detectable associated tremors. We show that a single asperity model with sudden stress drop followed by a rate strengthening effect damps the seismic radiation and increases event duration. We compute synthetic seismograms for our source model. The synthetic signal successfully reproduces the features of observed very low‐frequency earthquakes. Moreover, the synthetic very low‐frequency earthquake signal in 0.02–0.05 Hz is not accompanied by detectable tremor signals at 2–8 Hz. Our results help explain why in some cases we observe very low‐frequency earthquakes without accompanying tremor. Plain Language Summary: Earthquakes are generated wherever faults accommodate their relative motion in a stick‐slip manner. Outside this seismogenic zone, tectonic plates are thought to be moving past each other slowly, continuously, and silently, in a manner known as creep. Currently, a number of anomalous seismic events are observed at the edge of seismogenic zone. They are results of slow, transient movement along the fault, where the plates do not move as fast as in regular earthquakes. These seismic events are called slow earthquakes. So far, different types of slow earthquakes are identified. Very low‐frequency earthquake is one of them. It is still not clear whether different types of slow earthquakes share the same source processes. In this study, we set up a model for very low‐frequency earthquake. Our result suggests that very low‐frequency earthquake could have a different source from other slow earthquakes, such as tremor. Our finding contributes to a better understanding of the relationship between different types of slow seismic events and broad spectrum of fault behaviors. Key Points: Our dynamic rupture model reproduces very low‐frequency earthquake signal without associated nonvolcanic tremors A single asperity on fault with sudden stress drop followed by a rate strengthening effect can increase moment rate function duration Our results explain why in some cases we observe very low‐frequency earthquake accompanied with tremors, while in some cases, we do not